PENGARUH DISIPLIN DAN KEMAMPUAN KERJA TERHADAP KINERJA KARYAWAN MELALUI MOTIVASI SEBAGAI VARIABEL INTERVENING PADA PT. BANK MANDIRI TBK KANTOR CABANG A. YANI PALANGKARAYA - Iin Anggraini; Sri Rahayu; Sundjoto Sundjoto; Etin Puspitasari (POLITEKNIK LP3I JAKARTA, 2025)
Human resources (HR) are a key factor in determining the success of a company. Therefore, companies will be required to be more selective in choosing human resources who are able to show good performance. The purpose of this study was to determine and analyze the work discipline and work ability affect employee performance through motivation as an intervening variable at PT Bank Mandiri, Tbk Branch Office A. Yani Palangkaraya. This research method uses a quantitative approach, with questionnaire data collection. The population in this study are employees of PT Bank Mandiri, Tbk Branch Office A. Yani Palangkaraya. The population amounted to 165 PT Bank Mandiri, Tbk Branch Office A. Yani Palangkaraya, while the sample in this study amounted to 116 employees of PT Bank Mandiri, Tbk Branch Office A. Yani Palangkaraya. The type of sampling technique in this study is purposive sampling technique. The results showed that Work Discipline has a positive and significant influence on Employee Performance. Work Ability has a positive and significant influence on Employee Performance. Work Discipline has a positive and significant influence on Employee Performance with Work Motivation as an intervening variable. Work Ability has a positive and significant influence on Employee Performance with Work Motivation as an intervening variable. Work Discipline and Work Ability have a positive and significant influence on Employee Performance with Work Motivation as an intervening variable.